2016
DOI: 10.1371/journal.pone.0167577
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Binge Eating One Year after Roux-en-Y Gastric Bypass and Its Relationship with Excess Weight Loss

Abstract: BackgroundBariatric surgery is the most effective treatment for obesity classes II and III. However, some patients do not get the desired results or initially lose and then regain the lost weight. Identifying these individuals early on and treating them adequately remains a challenge. As binge eating directly affects food intake, the study of this symptom and its relation to bariatric surgery and its results is increasing, because it appears to have an influence on the results of surgery.ObjectivesThis study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…There were seven studies that measured binge eating outcomes at 12 months post‐surgery. Five out of these seven studies reported a reduction in binge eating symptoms from pre‐surgery, but two studies did not report whether changes were statistically significant . One study used a clinical assessment and found that pre‐surgery BED reduced from 100% to 8%; however, this study did not indicate whether this was a statistically significant reduction .…”
Section: Binge Eating Outcomesmentioning
confidence: 84%
See 2 more Smart Citations
“…There were seven studies that measured binge eating outcomes at 12 months post‐surgery. Five out of these seven studies reported a reduction in binge eating symptoms from pre‐surgery, but two studies did not report whether changes were statistically significant . One study used a clinical assessment and found that pre‐surgery BED reduced from 100% to 8%; however, this study did not indicate whether this was a statistically significant reduction .…”
Section: Binge Eating Outcomesmentioning
confidence: 84%
“…Binge eating is highly prevalent among bariatric surgery candidates and has been shown to range from 6% to 35%, with some studies reporting prevalence rates as high as 50% . Binge eating symptoms have been associated with weight regain, reduced weight loss, higher body mass index (BMI), poorer mental health, and persistent eating difficulties following bariatric surgery . The impact of binge eating on psychological and medical difficulties pre‐surgery and post‐surgery is noteworthy and highlights the need for further investigating this behaviour among bariatric surgery patients.…”
Section: Psychological Outcomes Following Surgical and Endoscopic Barmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to the dietary recommendations provided was shown to be an important predictor of successful weight loss outcome [ 18 ]. Presence of disordered eating behaviours, such as grazing [ 18 ] and bingeing [ 19 ], were associated poorer weight loss outcomes. Interestingly, among those who had low adherence to recommended dietary regiments, those who grazed not more than once per day had a weight loss success rate of 68.3%, as compared to 27.6% among those who grazed more than once [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…An RYGBP may fail when it's primary outcome is not achieved, whether this is resultant from either an insufficient weight loss from what is predicted [13][14][15] or the patient regains weight shortly after the procedure is performed.…”
Section: Authors' Contributionsmentioning
confidence: 99%